2016
DOI: 10.1016/j.rpped.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de frutas e vegetais associado a outros comportamentos de risco em adolescentes no Nordeste do Brasil

Abstract: There is a need of public policies aimed at encouraging the consumption of healthy foods among adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
12

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 22 publications
0
16
0
12
Order By: Relevance
“…Lowry et al 9 indicated that adolescents who engaged in at least 60 minutes of daily MVPA were more likely to eat fruits and vegetables at least 3 times a day. Silva et al 11 found that less active Brazilian boys were more likely to report low fruit and vegetable consumption. Similarly, our results showed that active adolescents had higher consumption of fruits.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Lowry et al 9 indicated that adolescents who engaged in at least 60 minutes of daily MVPA were more likely to eat fruits and vegetables at least 3 times a day. Silva et al 11 found that less active Brazilian boys were more likely to report low fruit and vegetable consumption. Similarly, our results showed that active adolescents had higher consumption of fruits.…”
Section: Discussionmentioning
confidence: 99%
“…This study found alarmingly low rates of fruit and vegetable consumption (over 70%), and high rates of alcohol (mild: 24.0%; excessive: 15.6%) and tobacco use (6.7%). Many factors influence the adoption of healthy behaviors, but the importance of PA to the adoption of other healthy behaviors has been equivocal, if not contradictory in previous studies [10][11][12][13][14][15][16][17] . The present study provides new insights into the associations between PA and various health risk behaviors in a sample of adolescents from a metropolitan city in Southern Brazil.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations